Bifosfonati e disfunzione renale. Issue 3 (September 2018) - Distefano, Giulio; Zanoli, Luca; Di Lullo, Luca; Basile, Antonio; Granata, Antonio
Disphosphonates and renal impairment Osteoporosis and chronic kidney disease (CKD) are two frequent pathological conditions in the adult and geriatric population and often coexist. These conditions have a significant negative impact on the quality of bone tissue, complicated by the coexistence of CKD and metabolic bone disease (CKD-MBD) and a greater incidence of fractures than the general population. Bisphosphonates are a class of drugs effective in preventing bone fractures by inhibiting tissue resorption by osteoclasts. Efficacy and tolerability have also been extensively studied in patients with mild CKD, but doubts remain on the renal safety profile in patients with advanced and terminal chronic nephropathy. In this article we conducted a review of the evidence currently available on PubMed. The studies published up to now on bisphosphonates approved for oral or parenteral use demonstrate that there are no significant effects on long-term renal function when administered to patients with eGFR values >30 mL/min/1.73 m 2 or >35 mL/min/1.73 m 2 . Nevertheless, acute, but for the most transient, changes of renal function are possible after endovenous infusion of ibandronate and zoledronic acid. Since controlled trials in patients with eGFR >30 mL/min/1.73 m 2 are not available, it is not possible to comment on the safety profile in this population.